Technologies of forming OFDM signals in modern information and communication systems - Zamula, A.A. (Radiotekhnika, 2018)
Technologies of forming signals used in communication and telecommunications systems are considered, and the analysis of promising technologies that can be used in wireless broadband access communication systems is given. It is shown that a widely used OFDM modulation scheme has a number of shortcomings that can lead to a decrease in the system efficiency indicators. Alternative signal generation technologies are presented, in particular, signal-based signal processing based on window signal processing (W-OFDM), which eliminate the shortcomings of the OFDM technology.